(untitled) (Universal Technical Journal of Lumbini International Academy of Science and Technology, 2025)
This research investigates the impact of post-earthquake rural housing reconstruction in Nepal, focusing on changes in housing sizes, typologies, and financial debt among affected families. It highlights a significant reduction (i.e. 61% of respondents have two-room houses after earthquake) in average house size from pre- to post-earthquake periods, driven by constraints related to time, resources, and financial capacities. The study reveals that reconstructed homes are notably smaller and often do not meet the spatial needs of households compared to their pre-disaster counterparts. The quantitative analysis, which involved random sampling of household data complemented by secondary data from literature reviews and project reports, uncovers several key findings: The average reconstruction cost per house is NRs 6,14,600 significantly exceeds the government grants provided, leading to increased household debt and financial strain. Changes in construction materials and housing typologies, 75% of respondents with SMM typology decreased to 9% after the earthquake and the BMC had increased to 61% from 2% which reflect that beneficiaries are more likely to have BCM typology. The study finds that the lack of consideration for settlement- level dynamics in reconstruction efforts has resulted in incomplete recovery, indicating the need for a more integrated approach. The research also assesses the applicability of Central Place Theory in the housing reconstruction process, suggesting that incorporating this theory could improve planning and contribute to more sustainable outcomes. Overall, the research provides valuable evidence for refining policies and strategies related to rural housing reconstruction. It advocates for a revised approach that considers settlement dynamics and aligns with the spatial needs of affected communities, aiming to enhance the effectiveness and sustainability of future reconstruction efforts both within Nepal and in similar contexts worldwide.